Detection of gold nanorods uptake by macrophages using scattering analyses combined with diffusion reflection measurements as a potential tool for in vivo atherosclerosis tracking - Ankri, Rinat (Int J Nanomedicine, 2015)
In this study, we report a potential noninvasive technique for the detection of vulnerable plaques using scatter analyses with flow cytometry (FCM) method combined with the diffusion reflection (DR) method. The atherosclerotic plaques are commonly divided into two major categories: stable and vulnerable. The vulnerable plaques are rich with inflammatory cells, mostly macrophages (MΦ), which release enzymes that break down collagen in the cap. The detection method is based on uptake of gold nanorods (GNR) by MΦ. The GNR have unique optical properties that enable their detection using the FCM method, based on their scattering properties, and using the DR method, based on their unique absorption properties. This work demonstrates that after GNR labeling of MΦ, 1) the FCM scatter values increased up to 3.7-fold with arbitrary intensity values increasing from 1,110 to 4,100 and 2) the DR slope changed from an average slope of 0.196 (MΦ only) to an average slope of 0.827 (MΦ labeled with GNR) (P<0.001 for both cases). The combination of FCM and DR measurements provides a potential novel, highly sensitive, and noninvasive method for the identification of atherosclerotic vulnerable plaques, aimed to develop a potential tool for in vivo tracking.